PROBLEMS OF PHYSICAL EDUCATION AND SPORTS IN HIGHER EDUCATIONAL INSTITUTIONS STUDENTS - Turdimurodov Dilmurod Yuldashevich (Proximus Journal Publishing, 2024)
The article examines the problems of physical education and sports of students. It defines the basic principles of physical education, its means and methods, the main problems and proposals for solving them.
Keywords: education; development; principles; methods